Creating a cultural brand in France: slam poetry as poésie démocratisée - Nolen, C (2018)
French slam poetry, or le slam, has developed into a uniquely French interpretation that privileges the original motivations behind the American poetry slam competition rather than the competitive format itself. Its practitioners take pride in slam’s capacity to represent any genre or style of oral poetic expression and orient their practice not around aesthetics, artistic conventions, or competition, but around slam’s ethos. Research on French slam has focused primarily on studying slam in social and educational contexts rather than on slam’s ontology. This thesis addresses this gap by identifying the core principles that constitute French slam through the use of a grounded theory based analysis of twenty years’ worth of public discourse around slam. Furthermore, to better understand how this ethos structures and organises le slam I argue that it is best understood as a brand, not genre, of oral poetry. This branding framework elaborates the aspects of slam that make it recognisable despite its inherent ambiguity and positions it within 21st century French cultural production. By employing a grounded theory approach I have been able to asses slam on its own terms in accordance with a cultural studies tradition to identify what is at the heart of slam as popular oral poetry. French slam is oriented around the concept of democratising poetry. However, at its core it is not just poetry as an aesthetic experience, but also the social experience of creating, sharing, and consuming poetry together. French slam is simultaneously social and creative, this duality informs all aspects of its practice. Slam is thus a meeting, or rencontre, of poetry and of people that manifests as a brand of democratised poetic expression. This thesis brings to cultural studies a new perspective on emergent popular art whilst elaborating the specificity of French slam poetry.